The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1056/nejmoa0907569
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Release Niacin or Ezetimibe and Carotid Intima–Media Thickness

Abstract: This comparative-effectiveness trial shows that the use of extended-release niacin causes a significant regression of carotid intima-media thickness when combined with a statin and that niacin is superior to ezetimibe. (ClinicalTrials.gov number, NCT00397657.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
378
3
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(396 citation statements)
references
References 40 publications
4
378
3
7
Order By: Relevance
“…171 A placebo-controlled clinical trial by Taylor et al examined whether extended-release niacin slows the progression and/or causes regression of angiographically assessed coronary atherosclerosis. 172 In patients with CHD or high risk of CHD receiving long-term statin therapy, additional treatment with extended-release niacin at a target dose of 2 g daily resulted in a regression of mean carotid intima-media thickness over 14 months. 172 174 A recent meta-analysis of 387 randomized-control trials implied that niacin is effective in reducing the risk of nonfatal myocardial infarction in individuals not treated with a statin, whereas on top of background statin treatment niacin failed to reduce cardiovascular events.…”
Section: Niacinmentioning
confidence: 97%
See 1 more Smart Citation
“…171 A placebo-controlled clinical trial by Taylor et al examined whether extended-release niacin slows the progression and/or causes regression of angiographically assessed coronary atherosclerosis. 172 In patients with CHD or high risk of CHD receiving long-term statin therapy, additional treatment with extended-release niacin at a target dose of 2 g daily resulted in a regression of mean carotid intima-media thickness over 14 months. 172 174 A recent meta-analysis of 387 randomized-control trials implied that niacin is effective in reducing the risk of nonfatal myocardial infarction in individuals not treated with a statin, whereas on top of background statin treatment niacin failed to reduce cardiovascular events.…”
Section: Niacinmentioning
confidence: 97%
“…172 In patients with CHD or high risk of CHD receiving long-term statin therapy, additional treatment with extended-release niacin at a target dose of 2 g daily resulted in a regression of mean carotid intima-media thickness over 14 months. 172 174 A recent meta-analysis of 387 randomized-control trials implied that niacin is effective in reducing the risk of nonfatal myocardial infarction in individuals not treated with a statin, whereas on top of background statin treatment niacin failed to reduce cardiovascular events. 175 Thus, available evidence does not support the routine use of niacin and statin combination therapy for the prevention of cardiovascular disease events.…”
Section: Niacinmentioning
confidence: 97%
“…Among these 59 surrogate endpoint trials that had a subsequent clinical endpoint trial, in 24 cases the clinical endpoint trial results validated the positive surrogate trials, while in 20 the subsequent clinical endpoint trial was negative (Table 3). 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 A negative surrogate endpoint trial was less likely to be followed by a positive outcome trial and we identified only 3 such examples ( P =0.02, Figure 2). …”
Section: Resultsmentioning
confidence: 99%
“…Ezetimibe reduces LDL cholesterol, and a large-scale trial to study its effects on clinical outcome is ongoing, but to date, it has failed to show any effect on measured atherosclerosis biomarkers [54,55]. Niacin (also known as nicotinic acid, vitamin B 3 ) increases HDL cholesterol and reduces LDL cholesterol, but has not been studied in well-designed trials with clinical outcomes.…”
Section: Dyslipidemiamentioning
confidence: 99%